Baseline prognostic factors affecting survival in recurrent and/or metastatic salivary gland adenoid cystic carcinoma. (March 2022) - Lombardi, Davide; Tomasoni, Michele; Lorini, Luigi; Gurizzan, Cristina; Tomasini, Davide; Ardighieri, Laura; Battocchio, Simonetta; Bozzola, Anna; Mattavelli, Davide; Paderno, Alberto; Zamparini, Manuel; Farina, Davide; et al.
Highlights: Baseline prognostic factors affecting survival in recurrent and/or metastatic salivary gland adenoid cystic carcinoma. Adenoid cystic carcinoma is a rare, indolent malignancy with poor long-term survival. Baseline features should be considered in prognostic stratification of relapses. Baseline lymphovascular invasion independently affected survival of relapsed patients. Adjuvant radiotherapy in the primary setting increases survival in recurrent patients. Whenever feasible, salvage surgery of locoregional recurrence should be pursued. Abstract: Objectives: Adenoid cystic carcinoma (AdCC) is a rare disease, with indolent behavior and poor long-term survival. Many studies have evaluated the role of clinical and pathological factors at presentation on the risk of recurrence. In this study we investigated whether baseline demographic, clinical, and pathological characteristics at the time of primary curative treatment could influence the prognosis of patients once local and/or distant recurrence occurred. Methods: All patients affected by primary salivary gland AdCC and treated with curative surgery from January 1997 to June 2016 were reviewed, evaluating those who later developed loco-regional recurrence and/or distant metastasis. Time from the first relapse to death (recurrent/metastatic overall survival, RMOS) was considered the outcome of interest. Results: Out of 87 surgically treated AdCC patients, 36 relapsing lesions were included. Median ages at first presentation and recurrence were 55 and 60-year-old, respectively; 58% were females. Median disease-free-interval (DFI) was 22.0 months. Five-year RMOS was 47%. At univariate analysis, age ≥ 60-year-old (HR:2.67, p = 0.030), primary tumor lympho-vascular invasion (LVI) (HR:5.38, p = 0.003), adjuvant radiotherapy (RT) in the primary setting (HR:0.37, p = 0.043), and DFI < 30 months (HR:3.94, p = 0.008) significantly affected RMOS. Multivariable analysis confirmed the presence of LVI and shorter DFI as independent risk factors. Conclusions: Knowledge of baseline clinicopathological features is helpful in the prognostic stratification of patients with recurrent AdCC, with LVI as the most relevant baseline factor. Adjuvant RT demonstrated its protective role on survival even once recurrence occurred, further supporting its adoption in the primary setting.